« Refonctionnaliser » les centres historiques des petites villes en décroissance : une quête d’attractivité basée sur la proximité servicielle - Alix de la Gaignonnière (GéoProximitéS)
This article looks at the ‘refunctionalisation’ of shrinking historic centres in France, i.e. the relocation of amenities. To this end, it analyses this refunctionalisation within the revitalisation plan for the historic centre of Villefranche-de-Rouergue (Aveyron), developed as part of the Action Cœur-de-Ville programme. The analysis is based on a corpus of local planning documents, grey literature, seven semi-structured interviews and INSEE statistical data. The article shows that the amenity proximity supported by this refunctionalisation is based on a logic of attractiveness and contributes to the social project of gentrification of the historic centre undertaken by Villefranche-de-Rouergue town council.